2007
DOI: 10.1038/sj.sc.3102116
|View full text |Cite
|
Sign up to set email alerts
|

Spinal pseudomeningocoele: a diagnostic dilemma

Abstract: Case report: A case of progressive sacral swelling in a paraplegic man who sustained spinal cord injury 14 years ago is presented. Although his clinical features were suggestive of pseudomeningocoele, we were unable to confirm the diagnosis preoperatively. Conclusion: Traumatic spinal pseudomeningocoele is very rare. Even with the available modern diagnostic imaging techniques, it is still difficult to diagnose a spinal pseudomeningocoele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It is reported that the diagnosis of pseudomeningocoeles is not always straightforward and a number of them are asymptomatic. 1 Post-exertional thoracic pseudomeningocoele in a 41-year-old woman: a rare cause of interscapular pain We present an unusual case of a previously healthy 41-year-old lady who acutely developed severe, disabling interscapular pain while lifting heavy boxes. She had no associated neurological deficits.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It is reported that the diagnosis of pseudomeningocoeles is not always straightforward and a number of them are asymptomatic. 1 Post-exertional thoracic pseudomeningocoele in a 41-year-old woman: a rare cause of interscapular pain We present an unusual case of a previously healthy 41-year-old lady who acutely developed severe, disabling interscapular pain while lifting heavy boxes. She had no associated neurological deficits.…”
Section: Discussionmentioning
confidence: 98%
“…In the former, CSF escapes from the subarachnoid space to lie in the extradural space, and in time becomes covered by a false capsule or in some instances an intact arachnoid layer, 1 while in the latter all layers of the meninges are present in the sac.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations